Pencegahan Bullying Melalui Edukasi Karakter Berbasis Empati pada Siswa SMPN 2 Buahdua - Herna Yuliana; Sri Mulyanti; Riva Aenatul Hasanah; Alif Milah Arifin; Desi Cahya Anggraeni (IKHTIAR: Jurnal Pengabdian Kepada Masyarakat, 2026)
Bullying remains a persistent social issue in school environments and has significant negative impacts on students’ psychological well-being, sense of safety, and character development. This community service activity aims to prevent bullying through empathy-based character education among students at SMPN 2 Buahdua. The program was implemented through a Participatory Action Research (PAR) approach involving students and school stakeholders as active participants in problem identification, program implementation, and reflection processes. The activities included stop bullying educational socialization, interactive discussions, simulations, and collective reflection emphasizing empathy, mutual respect, and social responsibility. The results indicate an increase in students’ awareness of bullying dangers, the development of empathetic attitudes in social interactions, and enhanced student participation in creating a safe and inclusive school environment. Therefore, empathy-based character education delivered through participatory approaches can serve as an effective preventive strategy in bullying prevention within school settings. In addition, the participatory learning process encourages students to actively express opinions, share social experiences, and develop critical awareness toward negative behaviors in peer interactions. The implementation of collaborative educational strategies also strengthens the role of schools as social institutions that promote positive character formation and foster harmonious interpersonal relationships among students in a sustainable manner.